The Evolution of Physical and Technical Performance Parameters in the English Premier League - Barnes, C.; Archer, D. T.; Hogg, B.; Bush, M.; Bradley, P. S. (International Journal of Sports Medicine, 2014)
This study examined the evolution of physical and technical soccer performance across a 7-season period in the English Premier League. Match performance observations (n=14 700) were analysed for emergent trends. Total distance covered during a match was ~2% lower in 2006–07 compared to 2012–13. Across 7 seasons, high-intensity running distance and actions increased by ~30% (890±299 vs. 1 151±337 m, p<0.001; ES: 0.82) and ~50% (118±36 vs. 176±46, p<0.001; ES: 1.41), respectively. Sprint distance and number of sprints increased by ~35% (232±114 vs. 350±139 m, p<0.001; ES: 0.93) and ~85% (31±14 vs. 57±20, p<0.001; ES: 1.46), respectively. Mean sprint distance was shorter in 2012–13 compared to 2006–07 (5.9±0.8 vs. 6.9±1.3 m, p<0.001; ES: 0.91), with the proportion of explosive sprints increasing (34±11 vs. 47±9%, p<0.001; ES: 1.31). Players performed more passes (35±17 vs. 25±13, p<0.001; ES: 0.66) and successful passes (83±10% vs. 76±13%, p<0.001; ES: 0.60) in 2012–13 compared to 2006–07. Whereas the number of short and medium passes increased across time (p<0.001; ES>0.6), the number of long passes varied little (p<0.001; ES: 0.11). This data demonstrates evolution of physical and technical parameters in the English Premier League, and could be used to aid talent identification, training and conditioning preparation.
Keywords: longitudinal; high-intensity; sprinting; passing; football